Implementation of the REACT Strategy Assisted by PhET Simulation to Improve Critical Thinking Skills on the Mechanical Wave Characteristics Topic - Ratu Zachrien Qalbia Dwi Ridwan; Ida Kaniawati; Heni Rusnayati (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2025)
This study examines the improvement of students' critical thinking skills through the REACT Strategy assisted by PhET Simulation. The research employs a quantitative method with a pre-experimental one-group pretest-posttest design. The sample consists of 35 purposively selected 11th-grade students from a high school in Bandung, studying the characteristics of mechanical waves. Instruments include an essay-based critical thinking test (eight questions), and Student Worksheets. Data were analyzed using N-Gain and effect size. Results show that the REACT Strategy with PhET Simulation yielded an N-Gain of 0.52 (medium category). The strategy was also effective in enhancing critical thinking skills, with a high effect size (d = 3.19). In conclusion, implementing the REACT Strategy assisted by PhET Simulation significantly improves students' critical thinking skills in learning.